STRATEGI GURU DALAM PENGELOLAAN KELAS YANG EFEKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Eka Sumbulatim Miatu Habbah; Elvira Nathalia Husna (Journal of Pedagogi, 2024)
This study aims to describe the teacher's strategies in the classroom that are effective in increasing student motivation. This study used a qualitative phenomenological approach with the research subject being a class III A teacher at SD Negeri No. 85/VII Semaran as much as one person. Data from this study were obtained through observation and interviews with class teachers and analyzed by classifying data, reducing data, presenting and drawing conclusions. The results showed that effective classroom management strategies implemented by teachers in increasing student learning motivation were reflected in optimizing effective classroom management, the desire and desire to succeed, the encouragement and need for learning, the hopes and aspirations for the future, the rewards for learning, there are interesting activities in learning, and there is a conducive learning environment. The research concludes that student learning motivation can be increased by the teacher's strategy in effective classroom management.